Failure detection and recovery in self-healing WSN. (2018) - Lakshmi, Chaganti B.N.; Rao, S. Krishna Mohan
In wireless sensor networks (WSNs), there are some problems of failures in self-healing network which need to be detected and recovered. So, there is need of failures detection and recovery technique for these failures. For this we propose correlation-based detection and self-healing based recover technique. The proposed technique, detects the communication backbone node failures and use self-healing policy for recovery. In the proposed technique, the mean values of sensor signals are used for correlation which detect inconsistencies in sensor inputs lucratively and having low false positives. We use self healing method for recovery which is able to recover both the backbone node failure and sentry node failure. This recovery technique is more reactive to node failures through considerable energy efficiency.